On the Toponym 'Asuka' and Conventional Epithet 'tobutori-no' in the Poems of the Poetic Anthology "Man'yoshu" - Motrokhov, A.I. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2011)
This article systematizes existing concepts about genesis of the toponym 'Asuka', observes its connection with the conventional epithet 'tobutori-no' and with the historical situation, which influenced its formation, on the basis of some poems of the first Japanese poetry anthology "Man'yoshu".
Keywords: auspicious sign; chronicle "Kojiki"; chronicle "Nihon Shoki"; conventional epithet 'tobutori-no'; era Shucho; poetry anthology "Man'yoshu"; the Imperial Palace "Asuka-no Kiyomihara-no miya"; toponym 'Asuka'